THE LONG-TERM EFFECT OF DEPRESSIVE SYMPTOMS ON ALL-CAUSE MORTALITY IN THE ELDERLY. (11th November 2018) - Lee, J; Jang, S; Cho, S
Abstract: This study aimed to identify the long-term effect of depressive symptoms on all-cause mortality in Korean older adults. The data used in this study were extracted from the baseline (2006) through fifth wave (2014) surveys of the Korean Longitudinal Study of Ageing (KLoSA). A total of 5, 501 older adults (2, 359 men and 3, 142 women) were ultimately included in the present analyses. Depressive symptoms were measured with the Korean version of the 10-item Center for Epidemiological Studies Depression Scale (CES-D 10). The person-time was calculated on a monthly basis based on the baseline survey point. Survival curves were generated using Kaplan-Meier analysis, and the Cox proportional hazards regression was conducted to predict the risk of all-cause mortality associated with depressive symptoms at baseline. The similar curves of survival probability due to depressive symptoms according to gender are presented, however, the effect of depressive symptoms on all-cause mortality was higher in men than women. Compared with the crude HRs, the effect of depressive symptoms is greater in men than in women, but this trend was reversed after controlling the covariates. Despite the differences of extent, the effect of depressive symptoms was statistically significant regardless of adjustment. In conclusion, the present study has demonstrated that the depressive symptoms affect the increased risk of all-cause mortality. Particularly, it has been confirmed that the risk of mortality associated with depressive symptoms was reduced by modifiable factors such as social participation. Therefore, spatial and policy environment should be created for the elderly to participate in society.